2019
DOI: 10.1002/imhj.21769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of male postpartum depression on father–infant interaction: The mediating role of face processing

Abstract: It is estimated that postpartum depression affects up to 25% of men. Despite such high prevalence, the majority of studies on postpartum depression are focused on mothers, and the role of paternal depression and its effects on infant development have been overlooked by researchers and clinicians. The present study aimed to fill this gap by investigating the effect of paternal postpartum depression on father–infant interactions. In addition, we examined whether differences in face recognition mediated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
0
14
0
5
Order By: Relevance
“…Further, depressive symptoms are negatively associated with physical care practices in mothers (e.g., feeding and sleep practices), and negatively associated with engagement in cognitively enriching activities (e.g., reading) in both mothers and fathers. Fathers with postpartum depression exhibit lower levels of responsive and sensitive parenting [30]. Dix and colleagues found evidence that offspring demonstrate a learned pattern of emotional withdrawal from mothers who are often unresponsive [31].…”
Section: Introductionmentioning
confidence: 99%
“…Further, depressive symptoms are negatively associated with physical care practices in mothers (e.g., feeding and sleep practices), and negatively associated with engagement in cognitively enriching activities (e.g., reading) in both mothers and fathers. Fathers with postpartum depression exhibit lower levels of responsive and sensitive parenting [30]. Dix and colleagues found evidence that offspring demonstrate a learned pattern of emotional withdrawal from mothers who are often unresponsive [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in relation to observational measures, paternal displays of negative affect assessed via. the GRS were higher in fathers in the depressed group (defined in this study as fathers with a positive SCID and/or BDI/EPDS depressive symptoms above the cut-off), compared to non-depressed, at 2-16 weeks (23). However, in another study no differences were reported between depressed (defined here as fathers with a positive SCID only) and non-depressed groups in the same construct, using the same measure, at 3-months (122).…”
Section: Performance Of Tools Used To Assess the Father-offspring Relmentioning
confidence: 75%
“…Nevertheless, difficulties in parenting that tend to be especially evident in the first postnatal year (18)(19)(20) manifest in many different forms. They may become apparent through the quality of the father-infant relationship-such as fathers attachment relationship with the fetus [e.g., (21,22)] behavioral disengagement and expression of negative affectivity [e.g., (23)(24)(25)], fewer mental state references in speech (26)-as well as quantity of paternal involvement-indexed by lower levels of engagement in positive enrichment activities and routine childcare [e.g., (10,27,28)]. In response infants may also alter their interactive behaviors with increased negative affect and avoidance, such as gaze aversion (23).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, la depresión posparto paterna (DPP-P) puede llegar a afectar hasta al 25% de los hombres tras el nacimiento de su bebé (Koch et al, 2019), lo que pone énfasis en la necesidad de que los padres sean evaluados y tratados durante el posparto. Se desconoce su prevalencia en España.…”
Section: Depresión Posparto Paterna: Una Nueva Entidadunclassified